Order Form and Information in Securities Markets. - Easley, David; O'Hara, Maureen (Journal of Finance, 1991)
This paper examines the effects of price-contingent orders on security prices. The authors show that a market maker who knows the type and composition of trades will set larger spreads and adjust prices faster than if price-contingent orders were not allowed. Because traders have rational expectations over the book, the authors demonstrate that uncertainty over order type reduces the variance of prices but with a corresponding loss in price informativeness. They also show that the sequence property of price-contingent orders increases the probability of large price movements. This distinction between variance and episodic price volatility has important policy implications.